Honeybees - Twist, Clint (Milwaukee, WI : G. Stevens Pub., 2006)
Explains what honeybees are, examines the anatomy of these busy insects, and describes the behaviors of honeybees as individuals and as colonies. Includes a look at additional types of bees.
Includes index.
Originally published: Tunbridge Wells, Kent, U.K. : Ticktock, 2006.
3.6
K-3
Keywords: Honeybee -- Juvenile literature; Bees; Honeybee; Bees; Honeybees